Dampak Penyelenggaraan Pendaftaran Merek Berdasarkan Asas First to File - Savira, Elsa (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2023)
Abstract One type of rights protected by Intellectual Property Rights (HKI) is trademark. In order to create legal certainty and legal protection of trademark rights to each legal subject, the Ministry of Law and Human Rights via DJKI organizes trademark registration based on the first to file rule. Implementation of trademark registration based on the first to file rule has had both positive and negative impacts. This research discusses trademark registration based on the first to file rule. In this regard, this research is focused on examining the negative impacts of carrying out trademark registration based on the first to file rule. This is a normative research. The method used is normative juridical. This research is prescriptive analysis, using various types of data in legal research. The results show that the negative impact of implementing trademark registration based on the first to file rule is in the form of the actions of individual legal subjects who submit applications for registration of trademark rights to the Minister of Law and Human Rights via DJKI, which violates the rights of legal subjects who use the trademark for the first time (first to use) Key words: impact, registration, trademark